SEKULARISASI DAN KETUHANAN - Snijders, Adelbert (UNIKA Santo Thomas, 2004)
By secularization we mean the process by wich sectors of society and culture are detached from religious institutions and symbols. Many religious institutions (schools, hospitals) are taken over by state. Conflicts between science and religion results a gap between science, philosophy and religion. For many people the process of seculariation has been a way to secularism. By secularism we mean ateism in the name of progress and liberation of human values (Comte, Feuerbach, Marx, Nietzsche, Sartre). For christians secularization is a challenge and a way for aggiornamento. There is no rivalship between science and philosophy, between science and religion. Each of them is otonomous. The field of science is the relation among fenomena. Philosophy asks about the Ground of â€˜all what isâ€™. The world has to be recognised as the world. God has to be recognised as God. â€œRender to Caesar the things that are Caeserâ€™s and to God the things that are Godâ€™sâ€ (Lk 20:25).